Trastorno de adaptación y su influencia en el estado emocional de una joven de 20 años, en el cantón Baba - Pérez Barros, Ginger Sugey (2022)
The present case study modality research work has as its theme: "Adjustment disorder and its influence on the emotional state in a 20-year-old girl", which aims to determine the influence of the adjustment disorder on the emotional state of the patient. For its development and obtaining results, different psychological tools were used, such as the observation sheet, clinical history; psychological interview, Coopersmith self-esteem questionnaire, depression self-measurement scale (EAMD), anxiety self-assessment scale (EAA), which collaborated in the diagnosis of the disorder that afflicted the adolescent. Situations framed according to the symptomatology of the disorder were detected; that was established by affected areas such as: cognitive field, affectivity, behavior, and somatic. Within the syndromic picture, the aspects that produced the most significant discomfort were nonconformity with her body, her problem adapting to her environment, not being able to easily relate to other people, her fear of being criticized by other people, her unusual behavior decreased interest in leaving home, excessive feelings of guilt and insecurity felt outside the home and the fear of being alone in it. As a solution to the problem, a therapeutic scheme was formulated with a focus on cognitive-behavioral techniques, aimed at improving the affective-emotional area, as well as social relationships, which produced significant and positive changes in the behavior and mood of the patients. the patient, despite the non-conclusion due to absenteeism to the therapeutic sessions.